Wild west 2.0 : how to protect and restore your online reputation on the untamed social frontier - Fertik, Michael; Thompson, David, 1979- (New York : American Management Association, 2010)
In the age of Wild West 2.0, everyone has an online reputation. This resource offers simple yet extraordinarily powerful ways to proactively protect one's online reputation and offset even the most savage attacks.
Includes bibliographical references and index.
Keywords: Personal information management; Online identities; Rumor; Internet in publicity; Public relations; Corporate image